THE IMPACTS OF COMMUNITY SERVICE ON STUDENTS’ SOFT SKILL DEVELOPMENT - Faraazlina, R.; Zunurain, Farah (Journal of Techno-Social, 2018)
This study is a survey to identify the impact of community service on students’ soft skill development. In addition, this study also identified the level and dominant soft skills that influence the students after their participation in community service activities. 65 respondents were involved in this study. The instrument for this study was a questionnaire that consists of two parts: background of respondents and research questions. There were 35 items for pre-test and post-test based on five soft skill elements: communication, teamwork, leadership, professional ethics and morality as well as entrepreneurship skills which were measured using a Likert scale. The data obtained were analysed descriptively and inferentially by using Statistical Package for Social Sciences Version 20.0 (SPSS) software. The results showed that the level of soft skills among the students involved in community service was as high as 3.70 out of 4.00. Meanwhile, the dominant element is professional ethics and morality compared to other soft skills elements. This study can be used as a guideline to organise high impact soft skills development for other programmes and activities in the future.